APPLYING THE STRATEGIC VISION APPROACH (FORESIGHT) IN SETTING PRIORITIES IN AGRICULTUREAND ENERGY IN VIETNAM - Bach Tan Sinh; Le Ba Nhat Minh; Nguyen Minh Tu; Nguyen Hong Quan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2023)
Addressing the challenges of inclusivity and sustainability in the context of the 2030 Agenda for Sustainable Development requires: (a) broaden the strategic focus of science, technology and innovation policy (STI) to mainstream social challenges into the core of the Program; (b) mainstreaming the direct and indirect contributions of innovations to the economic, social and environmental aspects of sustainable development; and (c) promote transformative innovations with the potential to replace existing unsustainable systems and practices. The article provides international experience in the application of the strategic vision approach (foresighting) to select priorities in agriculture and energy, toward sustainable development. Based on analyzing the status of the application of the Strategic Vision approach in Vietnam and international experiences, the article proposes some initial solutions for the application of the Strategic Vision approach in selecting priorities in agriculture and energy toward sustainable development in Vietnam. Code: 23011601